Prognostic indicators in clinically node-negative malignant primary salivary tumours of the parotid: A multicentre experience. (December 2021) - Fussey, Jonathan; Tomasoni, Michele; Tirelli, Giancarlo; Giordano, Leone; Galli, Andrea; Colangeli, Roberta; Cazzador, Diego; Tofanelli, Margherita; Da Mosto, Maria Cristina; Bianchini, Chiara; Pelucchi, Stefano; Ubayasiri, Kishan; et al.
Highlights: In parotid carcinoma, management of clinically node-negative neck is debated. Rate of occult nodal metastasis after elective neck dissection exceeds 22%. Older age, histology, high grade and stage are risk factors for occult metastasis. Adenoidcystic carcinoma should not be considered a low-risk tumour for nodal metastasis. Elective neck dissection should be performed in tumours with high-risk features. Abstract: Objectives: Nodal metastasis is an important prognosticator in primary parotid cancers. The management of the clinically node-negative neck is an area lacking consensus. This study investigates the occult nodal metastasis rate, and prognostic indicators in primary parotid cancers. Materials and methods: We performed a multicentre retrospective case note review of patients diagnosed and treated surgically with curative intent between 1997 and 2020. Demographic, clinic-pathological and follow-up data was recorded. Results: After exclusions, 334 patients were included for analysis, with a median follow-up of 48 months. The overall rate of occult lymph node metastasis amongst patients undergoing elective neck dissection was 22.4%, with older age, high-grade and more advanced primary tumours being associated with higher rates. On multivariable analysis, age ≥ 60 years (HR = 2.69, p = 0.004), high-grade tumours (HR = 2.70, p = 0.005) and advanced primary tumours (pT3-4, HR = 2.06, p = 0.038) were associated with worse overall survival. Occult nodal metastasis on final pathology was associated with a close-to-significant reduction in regional recurrence free survival (HR = 3.18, p = 0.076). Conclusion: This large series confirms the significant occult lymph node metastasis rate in primary parotid cancer, and demonstrates the importance of primary histology, tumour grade and stage in predicting survival outcome. This data supports the use of elective neck dissection in patients with high-risk tumours.